2020
DOI: 10.3390/fire3010007
|View full text |Cite
|
Sign up to set email alerts
|

Decomposing the Interactions between Fire Severity and Canopy Fuel Structure Using Multi-Temporal, Active, and Passive Remote Sensing Approaches

Abstract: Within the realms of both wildland and prescribed fire, an understanding of how fire severity and forest structure interact is critical for improving fuels treatment effectiveness, quantifying the ramifications of wildfires, and improving fire behavior modeling. We integrated high resolution estimates of fire severity with multi-temporal airborne laser scanning data to examine the role that various fuel loading, canopy shape, and other variables had on predicting fire severity for a complex of prescribed fires… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 51 publications
1
32
0
Order By: Relevance
“…It was hypothesised that the improved vegetation representation from LiDAR would mean that predictor variables describing height or layer count differences between pre-fire and post-fire would be used in the prediction of severity, particularly in areas of forest. This would support Hu et al [43], Hoe et al [44] and Skowronski et al [46], who demonstrated the effectiveness of describing changes to structural characteristics such as profile area and LiDAR return proportions 2 m above ground, pre-fire 95% heights and pre-fire return proportions 2 m above ground. However, the structural variables generated in this research showed only a small change between pre-and post-fire (Table 14).…”
Section: Severity Accuracysupporting
confidence: 74%
See 2 more Smart Citations
“…It was hypothesised that the improved vegetation representation from LiDAR would mean that predictor variables describing height or layer count differences between pre-fire and post-fire would be used in the prediction of severity, particularly in areas of forest. This would support Hu et al [43], Hoe et al [44] and Skowronski et al [46], who demonstrated the effectiveness of describing changes to structural characteristics such as profile area and LiDAR return proportions 2 m above ground, pre-fire 95% heights and pre-fire return proportions 2 m above ground. However, the structural variables generated in this research showed only a small change between pre-and post-fire (Table 14).…”
Section: Severity Accuracysupporting
confidence: 74%
“…Furthermore, the area was captured both pre-and post-fire allowing for a two stage classification: firstly classifying land cover and secondly classifying the severity within each land cover type, providing a testbed to explore the changes resulting from fire. Prior work from fixed wing and satellite remote sensing platforms have demonstrated the utility of imagery and supervised classifications to estimate fire severity across an area [43,44,46,[68][69][70]79]. McKenna et al [24], Simpson et al [26] and Carvajal-Ramírez et al [27] demonstrated the utility of UAS SfM image-derived variables from pre-and post-fire point clouds to map fire severity at local scales across areas with limited structural diversity (open grassland, woodland and peatland).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…), and huckleberry (Gaylussacia spp.). For a detailed description of the species assemblages of the New Jersey Pine Barrens [20,21] and examples of experimental fire behaviour and firebrand production, see [8] and [22]. This section first discusses the measured fire behaviour to provide context for the firebrand measurements.…”
Section: Field Measurement Of Firebrand Characteristics and Dynamicsmentioning
confidence: 99%
“…Remote sensing data and methods are also widely employed for post-fire mapping of the burned area, as well as for the post-fire characterization of wildfires in terms of fire severity [41][42][43]. Furthermore, the integration of data acquired by active sensors allows for the mapping of the vertical characteristics of the complex forest structure and can assist the process of characterizing and mapping forest fuels and post-fire damage assessment [44].…”
Section: Introductionmentioning
confidence: 99%